Effect of Tilt Table Training on Balance among Subjects with Basal Ganglia Bleed: A Pilot Study. - Rajbanshi, Surendra Kumar; Joshi, Diker Dev (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Basal ganglia bleed is a major cause of disability with 40% subjects suffering from moderate to severe disability. Among different treatments, mobilization on a tilt-table and functional training, which consisted of strengthening and stretching exercises of the limbs, postural control training in sitting and standing positions, therapist-guided techniques for facilitating normal movement, and simple forward stepping might have effect on balance in subjects with Basal ganglia bleed. Objective: To see the effect of tilt table mobilization and functional training on balance in subjects with basal ganglia bleed. Methodology: 10 subjects within age group of 18-65 years diagnosed with Basal ganglia bleed were included in the study based on inclusion and exclusion criteria. After measuring the baseline data, subjects were given mobilization on tilt table and functional training 30 minutes per session 5 days a week for 6 weeks. Pre and post measures of balance were assessed using dynamic gait index (DGI). Results: Mobilization on tilt table and functional training on balance in subjects with basal ganglia bleed showed statistically significant improvement in balance (p<0.05) on paired t test. Conclusion: Tilt table training can be beneficial for improving balance in subjects with basal ganglia bleed.